PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) SILATRI INDAH SEBAGAI PENGGERAK DESA BERAN MENJADI DESA YANG MANDIRI DALAM BIDANG EKONOMI - Agus Fatkhurohman; Kushandajani . (Journal of Politic and Government Studies, 2020)
BUMDES is a village business institution in the economic field that is managed by the community and the Village Government in an effort to strengthen the village economy and theeconomy of the village community which is formed based on the needs and potential of thevillage. This study aims to determine the management of BUMDes Silatri Indah and how itcontributes to creating an independent village in the economic field. The research method usedis a qualitative research with a descriptive approach. With data collection techniques throughinterviews with informants who are considered capable of providing detailed information aboutthe Management and Contribution of BUMDes Silatri Indah as an independent village moverin the economic field as well as through documentation that can support that information. Theresults of the study showed that BUMDes Silatri Indah was one of the best BUMDes inWonosobo Regency, because it was seen from various perspectives, such as good management,smooth business units, orderly administration and being able to contribute to the village. Themanagement process of BUMDes Silatri Indah is going well, this can be proven by planning,organizing and controlling which is not only done internally by BUMDes management but alsoto business units and business actors. While the contribution of BUMDes Silatri Indah inrealizing an independent village in the economic field can be seen through an increase inVillage Original Income (PADes) and being able to increase community income throughcommunity empowerment. Supporting factors include Natural Resources, Human Resources,Village Government Support and Cooperation with Other Parties. However, there are stillobstacles such as people's understanding of BUMDes and related capital. Keywords: Village-Owned Enterprises, Management, Contribution